P011 Improving time to treatment; a quality improvement project for results handling of non-standard GUM tests. (30th June 2016) - Parry, Laura
Abstract : Background: Delays to treatment following late non-standard results (NSR) review (e.g. mid-stream urine or radiological tests) by a doctor can cause patient harm. There are on average 10 NSR per week in our department. Prior to this project there was limited governance around clinician review of results with most done in an adhoc way sometimes causing significant delays to treatment (2+ weeks). Verbal communication with staff often did not result in NSR being actioned faster. Patients would often make multiple calls to the results team resulting in poor patient experience. Aim: All NSR, once available, will be actioned within 7 days by August 2015. Methods: Quality improvement (QI) methodology applied and key drivers identified: 1) Staff: Training, timetabled administration sessions. 2) Communication: Clear roles/responsibilities identified, email communication. 3) Timing: Timely upload of NSR onto recall list by results team. 4) Measurement: Recall list checked daily, NSR remaining recorded. Plan-do-study-act cycles (PDSA) were used over six months: PDSA 1: Developed a computerised recall system. Standard Operating Procedures (SOP) written. Team training. PDSA 2: Results team briefed/delegated task of recording remaining NSR. PDSA 3: SOPs uploaded to intranet. Email communication with new staff. SHO induction briefing (every four months). Results: We now have on average only one outstanding NSR per week. Verbal communication from the results team has confirmed much improved patient satisfaction. Discussion: Through QI methodology and the development of a simple organised governance system, patient care and satisfaction can be improved. Additional PDSA cycles are planned to further service improvement.